Comparison of the postoperative effect of low laser therapy and platelet rich fibrin on mandibular third molar surgery: a randomized study - Beste Erismen Agan; Lokman Onur Uyanık; Ceren Melahat Donmezer (BMC Oral Health)
Abstract Background This study investigates the postoperative benefits of low-level laser therapy (LLLT) and platelet-rich fibrin (PRF) in enhancing patient comfort and reducing complications after mandibular third molar extractions. Methods Sixty patients with vertically impacted mandibular third molars were randomly assigned to one control and three test groups (n = 15 each). In Group 1, PRF was applied to the socket post-extraction. In Group 2, PRF was combined with LLLT (B-Cure Dental Laser, 808 nm wavelength, 4 J/cm² energy density, continuous wave) applied extra-orally for three days post-surgery. Group 3 received LLLT alone. Group 4 (control group) underwent traditional osteotomy without additional treatments. All patients were prescribed 875/125 mg amoxicillin/clavulanic acid twice daily for five days. Results Postoperative parameters such as pain, swelling, analgesic use, and trismus were assessed on days 1, 2, 3, and 7. Significant improvements in pain, swelling, and trismus were observed in Groups 2 and 3 compared to the control (p < 0.001). Swelling was also significantly reduced in Group 1 compared to the control. Conclusions The study demonstrated favorable clinical outcomes in the LLLT and PRF groups, suggesting that both treatments could be promising strategies for improving postoperative recovery in terms of comfort and reduced complications. Trial registiration Clinicaltrials.gov ID: NCT06262945. The trial was first registered on 16/02/2024. Retrospectively registered.